Amidst mass atrocity and the rubble of theodicy : searching for a viable theodicy - Admirand, Peter J. (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2008)
This work assesses the theological and pastoral viability of key theodic texts within post-Holocaust Jewish thought, liberation theology, and Christian philosophical theodicy through textual analysis of testimonies from the Holocaust, communist gulags, Rwandan genocide, and other mass atrocities. My evaluation of the relevance of theodicy is based on two major presuppositions that I examine throughout the work; 1) theism needs to be able to articulate a viable theodicy; and 2) how a theodicy addresses and incorporates its theoretical limitations, or what I refer to as the fissures, gaps, and caesuras of a faith stance, is the fundamental evaluation of whether a theodicy can be considered viable. This investigation into the problem of evil highlights the need for a interdisciplinary, interreligious, and multimethodological approach that turns to both theodicists and antitheodicists and seeks to weave both pragmatic and theoretical approaches into the discussion. In this work of theodicy I have distinctively brought together current literary and cultural studies’ interpretations of these testimonies with a Catholic theological background. Also espoused here in this work is the practice of close textual reading to emphasise and interpret dominant meanings within various texts and to “tease out” any hidden or underdeveloped meanings or consequences to make connections and draw conclusions between many diverse texts and positions. This is a crucial practice when seeking to do justice to the victims who have lost all meaning in faith and God because of their ordeals along with those who maintain their faith or even believe because of those afflictions. Also noteworthy here is the selection of texts of theodicy and antitheodicy, with an aim to highlight the most persuasive and elemental features of both positions. Throughout I maintain that theists must share an antitheodicist’s scepticism of theodicy, but still must strive to develop a viable theodic response and so refute an antitheodicist’s claim that theodicy is immoral by justifying the unjustifiable, (unwittingly) colluding with some perpetrators of evil by sanctioning evil’s legitimacy, or falling prey to blaming the victim who has suffered enough.
Keywords: Religion and Theology, Ph.D.; Ph.D. Trinity College Dublin